Effect of Sorghum Flour and Anchovy Meal Substitution on Organoleptic Properties of Biscuits - Hassan, Tobianus; Mata, Irene Buy Mangngi (Media Publikasi Cendekia Indonesia, 2024)
Local foods in East Nusa Tenggara (NTT) Province are highly diverse, yet they remain underutilized for promoting health. Sorghum and anchovies, abundant in this region, present alternative sources for enhancing local nutrition, especially for toddler snacks. This study aimed to develop biscuits using local ingredients (sorghum and anchovies) as a potential snack for toddlers. The research employed an experimental design with a completely randomized design (CRD) consisting of four treatment levels: P0 (0% sorghum flour: 0% anchovy flour), P1 (30% sorghum flour: 10% anchovy flour), P2 (20% sorghum flour: 15% anchovy flour), and P3 (10% sorghum flour: 20% anchovy flour). The study occurred from January to May 2024 at the Nutrition Laboratory of Poltekkes Kemenkes Kupang. The results showed that the panellists’ preference for biscuit colour ranged from 3.82 to 4.04 (like), with P3 being the most preferred (4.04). The aroma scores ranged from 3.4 to 3.48 (somewhat like), with P2 receiving the highest score (3.48). Texture preference ranged from 3.9 to 4.1 (like), with P1 being the most preferred (4.1). Taste preferences ranged from 3.5 to 3.76 (like), with P3 scoring highest (3.76). In conclusion, biscuits with 20% sorghum flour and 10% anchovy flour (P3) were the most favoured overall, containing 1,111.6 Kcal of energy, 41.75 g of protein, 50.74 g of fat, and 123.51 g of carbohydrates. These findings suggest that locally sourced ingredients can be effectively used to create nutritious and appealing snacks for toddlers.